A channel for ion irradiation of materials at the accelerator “Sokol” - Glazunov, L.S.; Goncharov, A.V.; Zats, A.V.; Karpus’, S.G.; Kuz’menko, V.V.; Levenets, V.V.; Pistryak, V.M.; Sukhostavetz, V.I. (Вопросы атомной науки и техники, 2006)
At the accelerator “Sokol” a channel for ion irradiation of materials is constructed. The channel comprising a
beamline system, a slit device, an electrostatic scanning system with power and control modules, and an irradiation
chamber is placed behind the analyzing magnet. The main technical parameters of the channel are the following:
ions used – H, He, N, Ar; ion energy – 0.2…2 MeV; ion beam current – 2 µA; target zone being irradiated – from 2
×2 mm up to 40×40 mm; target holder temperature – 80…450 K. Irradiation channel tests are performed together
with experiments on polyimide films irradiation with hydrogen ions with an energy of 400 keV. На ускорителе «Сокол» создан канал ионного облучения материалов. Канал установлен после анализирующего магнита и состоит из ионопровода, щелевого прибора, электростатической сканирующей системы с блоком питания и управления, камеры облучения. Основные технические параметры разработанного устройства следующие: используемые ионы Н, He, N, Ar; энергия ионов 0,2…2 МэВ; ток пучка до 2 мкА; площадь облучения образца ─ от 2×2 мм до 40×40 мм; температура держателя образца ─ от 80 до 450 K. Проведены испытания канала облучения и выполнены эксперименты по облучению полиимидных пленок ионами водорода с энергий 400 кэВ. На прискорювачі «Сокіл» створений канал іонного опромінювання матеріалів. Канал встановлений після
аналізуючого магніту і складається з іонопроводу, щілинного пристрою, електростатичної скануючої
системи з блоком живлення і управління, камери опромінювання. Основні технічні параметри розробленого
пристрою наступні: іони, що використовуються, ─ Н, He, N, Ar; енергія іонів ─ 0,2...2 МеВ; струм пучка ─
до 2 мкА; площа опромінювання зразка ─ від 2×2 мм до 40×40 мм; температура утримувача зразка ─ від 80
до 450 K. Проведені випробування каналу опромінювання та експерименти по опромінюванню поліімідних
плівок іонами водню з енергією 400 кеВ.